Measuring Drivers of Procrastination in Academic Student - Wijanarko, Abi Dzarr Alghifari; Welly, John (Journal of Business and Management, 2015)
Abstract. Procrastination is the lack or absence of self-regulated performance and the tendency to deny or completely avoid an activity under one’s control (Tuckman & Sexton, 1989). MARS, also known as model of individual behavior, are model used to understand on what drivers can form an individual behavior. It consist of four factors which are motivation, ability, role perceptions, and support/situational factors).As an organization, academic institution need to know the drivers of behavior that might affect their academic members performance, including student. By creating a Procrastination Scale to measure procrastination level and Academic Motivation Scale into MARS model this research gather a 116 sample of academic student in SBM ITB. The result shows that Amotivation (r=.187) and Motivation External of external regulation (r=.197) has positive correlation with procrastination level. Using hierarchical regression analysis, the result further show that amotivation (b=.197) act as the most dominant contributor to procrastination level. External Motivation of external regulation (b=.126) follows as the second contributor while Situational Factors (b=-.127) shows as counter contributer of procrastination. As organization SBM ITB might want to further motivate their student and give tutoring about managing academic and non-academic activities. SBM ITB might also want to maintain their support to students to avoid further problem about increasing procrastination level. Keyword: motivation, ability, role perception, situational factor, procrastination, academic, organization